Scarlett Products Booming: Does Experiential Marketing Matter? - Christian Kuswibowo; Catur Erty Suksesty; Febrina Mahliza; Yennida Parmariza; Muhammad Faisal Anwar (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2023)
The study intentions to observe and analyze the effect of Brand Image and Product Quality on Purchase Intention of Scarlett products through Experiential Marketing as the Variable of Intervening. Causal research method was used here in order to define if there is any causal relation from independent to dependent variables. Data collection technique was benefitted the questionnaire. The population chosen were users of Scarlett products in West Jakarta area. The sample of this research is the consumers who use the Scarlett product with a total of 100 respondents who were selected randomly using random sampling technique. The Structural Equation Model was used as the research approach with Smart-PLS 3.2.8 version analysis research tool. It is found that Brand Image influenced both Purchase Intention and Experiential Marketing positively and significantly. Product Quality effected both Experiential Marketing and Purchase Intention significantly and positively. Experiential Marketing proved to effect Purchase Intention positively and significantly as the implication, Experiential Marketing should be maintained more broadly to increase Purchase Intention.